Pertumbuhan Ikan Tongkol Abu-Abu (Thunnus tonggol Bleeker, 1851) yang Tertangkap di Perairan Selat Bali - Made Ayu Pratiwi; Gde Raka Angga Kartika (Journal of Marine and Aquatic Sciences, 2022)
Longtail Tuna (Thunnus tonggol) in the waters of the Bali Strait is a by-catch fish, so that information on this fish resource was still very lacking and its management of longtail tuna was often neglected. The aimed of this study is to predict the signs of the unsustainability of longtail tuna resources based on growth aspects which include the distribution of length frequency, estimation of age groups, growth patterns and growth parameters. Data collection was carried out from December 2018 to February 2019. The growth pattern estimated by relationship of length and weight, cohort was identified using an analytical model based on the FISAT program (FAO I-CLARM Stock Assessment Tools) and growth parameters were analyzed using the Von Bertalanffy growth model. It can be seen that, the catch is dominated by the size of the fish that have matured gonads or adults (69% females and 73% males). The growth pattern of female and male of longtail tuna is negative allometric (length growth is more dominant than weight). So it can be assumed that there is an inconvenience in environmental conditions and competition in fighting for food and space in the waters of the Bali Strait.Longtail tuna had asymptotic length values of 784.71 mm (female) and 738.04 mm (male) with growth coefficients of 0.13 (female) and 0.18 (male). The growth performance inteprated as quite high when compared to other waters in Indonesia.